Penerapan Model Project Based Learning Menggunakan Media Canva Untuk Meningkatkan Kreatifitas Pada Mata Pelajaran Bahasa Inggris - Neneng Sri Lestari (Jurnal Sintaksis, 2022)
Learning English is very important because English is spoken internationally. Most of knowledge about science and high technology is written in English. Because of this, English, which is taught as a foreign language in Indonesia, is a compulsory subject in junior high schools, high schools and universities. Students are less creative in English lessons, so the right media is needed to increase the creativity of Al Maksum Stabat Vocational High School students. The Canva application is the right medium to increase student creativity. The topic of this research is the development of learning media using the Canva application to increase the creativity of Al Maksum Stabat SMK students in English subjects. With the aim of increasing student creativity in speaking English through the application of learning media using the Canva application. The stages of the research method are carried out in four stages, namely planning, action, observation and reflection. The results of the study concluded that the average student scores increased during the pre-test, cycle I and cycle II, namely 16.67, 51.34 and 85 and the percentage of student success increased from 0%, 46.67% to 100%. The results of the observation sheets and questionnaires also prove that the Project Based Learning learning model using Canva media has significantly succeeded in improving their abilities in English courses.